Foreign Language Anxiety among 12th Grade Senior High School Students - Muhammad Taufiqur Rachman (Retain: Journal of Research in English Language Teaching, 2025)
Anxiety appears to be a significant barrier for students learning English, as it can lead to negative self-perceptions and impact various factors essential to the learning process. Consequently, students may fail to attain a high or expected level of English proficiency, particularly in terms of speaking fluency. Twelfth-grade students at a private senior high school in Surabaya report experiencing fear or anxiety when speaking English, largely due to the challenges involved in communicating with teachers and peers during the English learning process. The aim of this study is to examine the levels of English speaking anxiety among twelfth-grade students at this private high school. Employing a descriptive quantitative approach, the study utilized a structured questionnaire to address the research questions and gather data. The instrument used was the Foreign Language Classroom Anxiety Scale (FLCAS), which comprises 33 items specifically designed to assess English speaking anxiety. A total of 173 students participated in the study, selected through convenience sampling. Findings revealed that 133 students exhibited moderate anxiety levels, 29 students demonstrated low anxiety, and 11 students experienced high anxiety. Key factors influencing anxiety included comprehension difficulties in communication, anxiety related to testing, and fear of negative evaluation. The results have important implications for English learners who experience speaking anxiety, as well as for their instructors. These insights may contribute to the development of more effective teaching strategies and improve educators’ understanding of student anxiety in the language learning context.